Contemplation and perception energy transition states - Yupapin, Preecha (International Journal of Scientific World, 2015)
In this paper, the concept of meditation and perception energy transition states is configured described by the spirit energy transitions. Being life has been jeopardized situation due to the chaotic society. The technique that can be used to release and recover such problems is the challenge and being proposed. There are two techniques that can lead to obtain the mind concentration, where they are meditation ad mind-body considerations that have been successfully used for years. The descriptions of meditation and perception are performed by the spirit energy transitions of eight and sixteen levels respectively. The transition states and energy levels are explained, which can be useful for practitioners and world society.